Practice of Naturalism in Naguib Mahfouz’s Midaq Alley - Wulandari, Betty Ayunda; Surur, Misbahus (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
Naturalism novels portray the reality of life in a sharper and more decisive way than realism novels. Naturalism takes the place of building a narrative, like shooting a photographic reality by zooming in. Narrative naturalism normally provides a sharp depiction of reality without idealization. This study identified the description of reality through elements of naturalism in the novel Midaq Alley by Naguib Mahfouz. This study deployed Emile Zola’s naturalism theory with a qualitative descriptive approach. The primary data source was the novel Midaq Alley by Naguib Mahfouz, supported by secondary data from relevant books and journal articles. The data were in sentences or paragraphs collected by reading and note-taking techniques. The results of this study figured out the elements of naturalism in the novel Midaq Alley by Naguib Mahfouz, including aspects of objectivity, setting, determinism, pessimism, and plot twists. The provisions for selecting these elements were based on findings practiced in writing the novel Midaq Alley. The novelty of this article lies in the discovery of elements of Emile Zola’s naturalism in the novel Midaq Alley by Naguib Mahfouz and the evidence of a picture of the postwar situation of Egypt depicted in real, alive, but natural by the author.